Seroprevalence of antibodies to astrovirus in chickens in Grenada, West Indies - Ravindra Nath Sharma; Romane Dufayet; Thomas Maufras; Kathryn O' Connell; Keshaw Tiwari (Veterinary World, 2017)
Aim: Chicken astroviruses (CAstV) are known to cause mild gastroenteritis, growth depression, and even mortality in poultry, especially in chickens, turkeys, and ducks. To the best our knowledge, there is no published information on CAstV in Grenada. This study was conducted to determine the prevalence of astrovirus in chickens in Grenada.